PENGARUH KOMITMEN ORGANISASI, KEPUASAN KERJA DAN KEPRIBADIAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. TALENGGAK JAYA FARM PAYAKUMBUH - Septini Atik; Machasin Machasin; Nuryanti Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of organizational commitment and job satisfaction on organizational citizenship behavior on employees of PT. Talenggak Jaya Farm in Payakumbuh, West Sumatra province. The population and sample in this study include all employees at Farm, amounting to 60 people. Primary data were collected by questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study was to use multiple linear regression analysis with the help of SPSS program. The sampling technique that I use is the census technique in which the entire population is sampled in this study. Based on the testing that has been done, the partial regression test (t) shows that all the independent variables studied: organizational commitment, job satisfaction and personality have a significant effect on organizational citizenship behavior. Meanwhile, the simultaneous regression test (F) shows that the three independent variables simultaneously affect the dependent variable with (R2) 64.7%, the rest is influenced by other variables outside of this study.Keywords: Organizational commitment, job satisfaction, personality, OCB